2017
DOI: 10.3389/fpls.2017.00775
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Identification of Orthologous ZIP Genes Associated with Zinc and Iron Translocation in Setaria italica

Abstract: Genes in the ZIP family encode transcripts to store and transport bivalent metal micronutrient, particularly iron (Fe) and or zinc (Zn). These transcripts are important for a variety of functions involved in the developmental and physiological processes in many plant species, including most, if not all, Poaceae plant species and the model species Arabidopsis. Here, we present the report of a genome wide investigation of orthologous ZIP genes in Setaria italica and the identification of 7 single copy genes. RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Therefore, biofortification of cereals or increasing their bioavailability in the edible parts like endosperm can cost-effectively solve the problem of malnutrition and save millions of lives across the globe 35 . Among the Fe and Zn superfamily, genes such as YSL, ZIP, NRAMP, FER, NAS have been identified in many plants like Arabidopsis thaliana 36 , Setaria italica 29 and Oryza sativa 28 . These genes were responsible for Fe and Zn translocation from soil to the grain filling sight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, biofortification of cereals or increasing their bioavailability in the edible parts like endosperm can cost-effectively solve the problem of malnutrition and save millions of lives across the globe 35 . Among the Fe and Zn superfamily, genes such as YSL, ZIP, NRAMP, FER, NAS have been identified in many plants like Arabidopsis thaliana 36 , Setaria italica 29 and Oryza sativa 28 . These genes were responsible for Fe and Zn translocation from soil to the grain filling sight.…”
Section: Discussionmentioning
confidence: 99%
“…In Oryza sativa, 17 ZIP genes 47 , 15 in Arabidopsis thaliana 10 , 12 in Poncirus trifoliata 48 , and 9 in Zea mays 46 were reported. Alagarasan et al 29 on the other hand, identified 36 ZIP family members in Setaria italica. In contrast, in the present study, 8 ZIP family members (out of a total of 29 iron and zinc transporter genes) were noticed in the genome of P. glaucum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, the information about ZIP genes is limited. Alagarasan et al (2017) identified seven SiZIP genes (SiZIP1-SiZIP7) in foxtail millet. The expression pattern of seven SiZIP genes was analyzed in root, leaf, stem and spica tissues of foxtail millet grown under drought stress without any additional nutrient supplementation.…”
Section: Foxtail Milletmentioning
confidence: 99%
“…With the conserved bZIP domain, bZIP family is one of the largest transcription factors in plants. The bZIP domain contains two structural features, a basic region and a leucine zipper ( Alagarasan et al, 2017 ; Zha et al, 2017 ). The basic region consists of about 16 amino acid residues and an invariant N-x7-R/K motif, which are responsible for nuclear localization and DNA binding, respectively.…”
Section: Introductionmentioning
confidence: 99%